2018
DOI: 10.1504/ijsom.2018.10009105
|View full text |Cite
|
Sign up to set email alerts
|

Work life balance of women employees: a literature review

Abstract: The review of literature on work life balance of women employees has been outlined up in view of its increased popularity with the major objective to have prosperity of society. WLB is a major concern for women employees in today's scenario, as extended work hours in the organisation pulls women employees' productivity and time which they actually meant to devote to their family sphere. The researcher has reviewed the literature on work life balance (WLB) of women employees with regard to significance of WLB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 190 publications
(327 reference statements)
0
1
0
Order By: Relevance
“…Clark ( 2001) defines WLB as satisfaction and good functioning at work and home with a minimum of role conflict. Considering the dual role of women in Indian society on the family and work front, WLB has become a major concern for women employees in today's scenario as extended work hours in the organization constraints their productivity and time meant to be devoted at the family front (Vasumathi, 2018). Research has found that WLB of employees increases various employee and organizational-related job outcomes (Sirgy and Lee, 2017) including job satisfaction.…”
Section: Work-life Balance and Job Satisfactionmentioning
confidence: 99%
“…Clark ( 2001) defines WLB as satisfaction and good functioning at work and home with a minimum of role conflict. Considering the dual role of women in Indian society on the family and work front, WLB has become a major concern for women employees in today's scenario as extended work hours in the organization constraints their productivity and time meant to be devoted at the family front (Vasumathi, 2018). Research has found that WLB of employees increases various employee and organizational-related job outcomes (Sirgy and Lee, 2017) including job satisfaction.…”
Section: Work-life Balance and Job Satisfactionmentioning
confidence: 99%